Synthesis and characterization nitrogen-doped carbon dots from candlenut shells using hydrothermal and solvothermal methods - Riska Riska; Marpongahtun Marpongahtun; Saharman Gea (Pascasarjana Universitas Negeri Medan, 2024)
Candlenut shells can be utilized as precursors for Carbon Dots (CDs) since new nanoscale materials have been proven using lignin, cellulose, hemicellulose, and carbon present in candlenut shells. A carbon substance smaller than 10 nm in size, CDs have special optical properties. This research focuses on the synthesis of CDs and Nitrogen Carbon Dot (NCDs) from hazelnut shell using urea passivation agent by hydrothermal and solvothermal methods, to determine the effect of solvent on the emission produced by CDs and NCDs. Hazelnut shell was carbonized at 300°C for 6 hours. The synthesis of CDs and NCDs was carried out at 220°C for 8 hours, then sonicated at 75°C for 30 minutes. The synthesis results were centrifuged at 5000 rpm for 30 minutes, filtered using Whatman No.42 filter paper. Analysis with a 365 nm UV lamp produced bluish green luminescence, brighter luminescence was shown in NCDs by solvothermal method. UV-Vis spectra showed absorbance peaks of 289-309 nm for CDs and 335-350 nm for NCDs. FTIR spectra of CDs and NCDs produced OH, CH, C=C, C=O, C-N, CO, and C-O-C functional groups. Photoluminescence analysis showed emission peaks of CDs and NCDs at 494 nm and 496 nm for hydrothermal method, for solvothermal method at 418 nm and 432 nm. CDs and NCDs with hydrothermal method showed higher intensity than with solvothermal method. The quantum yield values obtained were 11.4226% and 25.7419% and 10.2555% and 11.7473% for hydrothermal and solvothermal methods, respectively. Solvothermal method was effective for the synthesis of CDs and NCDs with brighter luminescence.